Evaluasi Program Muchadloroh Kubro dengan Model CIPP di Pondok Pesantren An Nawawi Berjan Purworejo - Zahra, Raihana; Suwadi (Universitas Negeri Yogyakarta, 2025)
The Muchadloroh Kubro Program at the An Nawawi Berjan Purworejo Islamic Boarding School is a program to train grammar and public speaking. The languages used are Arabic, English and French. . This program has been running since 2022, but there has been no detailed and comprehensive evaluation regarding this program. This research aims to determine the results of the evaluation of the Muchadloroh Kubro program at the An Nawawi Islamic Boarding School using the CIPP framework as a reference criterion. The type of research used is evaluative research with a qualitative approach, data collection using observation, interview and documentation techniques. Meanwhile, analyzing data is carried out by collecting data, reducing data, presenting data, drawing conclusions and verifying data. The results of the CIPP model evaluation in this research show that the intensive program in the Muchadloroh Kubro Program at the An Nawawi Islamic Boarding School has been implemented well. Of the four components, the Context and Product components are in the very good category, while the other two components, namely Input and Process are in the good category. Based on these results, it is recommended that the implementation of the intensive program must be continued with certain notes.